Limitations and Opportunities in Open Laryngeal Organ Preservation Surgery: Current Role of OPHLs - Succo, Giovanni; Crosetti, Erika (Frontiers in Oncology, 2019)
The current trend of treatment for intermediate-early advanced laryngeal cancer (LC) focuses on maintaining good locoregional control while also preserving a functional larynx. This goal can be achieved by adopting open laryngeal organ preservation surgery (OLOPS), at present mainly represented by open partial horizontal laryngectomies. Strict selection criteria, based on locoregional tumor extent as well as on the patient’s general condition, allow excellent oncological outcomes in untreated patients. Similar outcomes, albeit slightly worse, are also obtainable in radio-recurrent and laser-recurrent patients. The limitations for extensive application of this therapeutic strategy are to be found in the complexity of post-surgical in-hospital management and in the variability of functional results. The future direction is represented by simplification of the indications identifying iso-prognostic sub-categories within the T-stage, wider consensus on rehabilitation protocols, hybrid approaches to the larynx, and open minimally invasive access.